Evidence for subsurface ordering of oxygen vacancies on the reduced CeO2 (111) surface using density-functional and statistical calculations - Murgida, Gustavo Ezequiel (2013)
Oxygen vacancies on ceria (CeO2) surfaces play a crucial role in catalytic applications, yet whether vacancies are at surface or subsurface sites on reduced CeO2 (111) , and whether vacancies agglomerate or repel each other, is still under discussion, with few and inconsistent experimental results. By combining density-functional theory (DFT) in the DFT+U (U is an effective onsite Coulomb interaction parameter) approach and statistical thermodynamics, we show that the energetically most stable near-surface oxygen vacancy structures for a broad range of vacancy concentrations, Θ (1/16 ≤ Θ ≤ 1 monolayer) have all vacancies at subsurface oxygen sites and predict that the thermodynamically stable phase for a wide range of reducing conditions is a (2×2) ordered subsurface vacancy structure (Θ=1/4). Vacancy-induced lattice relaxations effects are crucial for the interpretation of the repulsive interactions, which are at the basis of the vacancy spacing in the (2×2) structure. The findings provide theoretical data to support the interpretation of the most recent experiments, bringing us closer to solving the debate.